A simple regression based approach to estimate deformation modulus of rock masses - Alemdag, Selcuk; Gurocak, Zulfu; Gokceoglu, Candan (Pergamon-Elsevier Science Ltd, 2015)
Rock mass characterization has a crucial importance in rock engineering applications including foundation design, slope design, support design and others. For these purposes, it is necessary to determine some input parameters for design, such as deformation modulus (E-m), uniaxial compressive strength (sigma(ci)) and Poisson ratio (upsilon). The E-m is an important input parameter and the practical and economical way to determine this parameter is to apply a rock mass classification system and estimate using the rock mass properties. Data from four different sites were used in the study. The values of E-m were calculated using the existing empirical equations based on the Rock Mass Rating (RMR89) system. Furthermore, pressuremeter tests were carried out to determine the E-m in one of the sites. The relationship between the RMR89 and the E-m was obtained via simple regression analysis using the E-m calculated from empirical equations based on RMR89 system. Afterwards, performance of the equation obtained from regression analyses was examined and compared the predicted Em values with experimental values with respect to the R-2 values using the data of fourth site. Overall R2 value was found to be as 0.75. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Deformation modulus; Rock Mass Rating; Pressuremeter tests; Regression analyses